Sensitivity to reward and punishment and alcohol outcomes: Metacognition as a moderator. (December 2019) - Sistad, Rebecca E.; Simons, Raluca M.; Simons, Jeffrey S.
Abstract: Introduction: The purpose of this study was to examine associations between inhibitory (sensitivity to punishment [SP], adaptive metacognition) and facilitatory (sensitivity to reward [SR], maladaptive metacognition) factors of alcohol consumption and problems among young adults. Methods: Three hundred fifty-five young adults (ages 18–25, 61% female) recruited from Amazon Mechanical Turk and a large public midwestern university in the United States self-administered a Web survey. Two multiple regression models were tested. Results: SR significantly moderated the effects of SP and the maladaptive metacognition (MC) subscale Uncontrollability/Danger on alcohol consumption. Alcohol problems were also significantly predicted by SR and Uncontrollability/Danger. The interaction between SR and SP on alcohol problems was conditional upon levels of the maladaptive MC subscale Lack of Cognitive Confidence, with a significant moderating effect only at high levels of Lack of Cognitive Confidence. Conclusions: Consistent with the literature, individuals with high levels of SR coupled with low SP are at risk for increased alcohol consumption. This effect on drinking behaviors is further influenced by maladaptive MC, such that individuals characterized by high SR and low SP are significantly more likely to report more alcohol-related problems if they believe that worrying is dangerous and uncontrollable or lack cognitive confidence; however as SP increases, this effect significantly diminishes. Highlights: The association between SP and alcohol consumption is moderated by SR. Beliefs of uncontrollability and SR increase alcohol consumption and problems. The interaction of SR, SP, and alcohol problems is moderated by cognitive confidence.